Marian Tonis: ANALISIS SISTEM MANAJEMEN LOGISTIK OBAT DI INSTALASI FARMASI RUMAH SAKIT PROF. DR. TABRANI PEKANBARU - Marian Tonis; Ani Riza Wati; Wiwik Suryandartiwi; Bobi Handoko (Journal of Hospital Administration and Management, 2021)
Drug logistics management in hospitals is the most important aspect that must exist in a hospital including the stages of planning, procurement, storage, distribution, elimination, evaluation and monitoring which are interrelated with each other. Prof. Hospital. Dr. Tabrani has several problems, especially in pharmacy installations, namely insufficient budget, insufficient human resources and SIMRS that are not optimal. The purpose of this study was to analyze the existing management system in the Pharmacy Installation of Prof. Hospital. Dr. Tabrani.This research uses a qualitative research type, conducted at Prof. Hospital. Tabrani, using in-depth interviews, observation and document review methods with 4 informants, namely the Head of Medical Support, Head of Pharmacy Installation, Person in Charge of Pharmacy Warehouse, and Pharmacy Staff. Data processing is done by reducing data, presenting data, and drawing conclusions. For data validation used source triangulation, method triangulation, and data triangulation.The results showed that the management of drug logistics in the Pharmacy Installation of Prof. Hospital. Dr. Tabrani has not been effective. This can be seen from the input components, namely inadequate human resources, budget costs that have not been understood by all parties responsible for the management of pharmaceutical preparations, pharmaceutical warehouses that still do not meet the standards properly.It is recommended that the Hospital Pharmacy Installation of Prof. Dr. Tabrani pays more attention to the drug logistics management system at the Pharmacy Installation of Prof. Hospital. Dr. Tabrani especially regarding the quantity and quality of human resources and infrastructure.